2002
DOI: 10.1002/ajhb.10065
|View full text |Cite
|
Sign up to set email alerts
|

Somatic comparisons of South Korean children and youths born and reared in a rural area with the descendants of rural to urban migrants

Abstract: During April-May 2000 somatic data were collected on 236 males and 191 females ages 6, 9, 13, and 15 years residing in rural areas around the communities of Ankye, Euisung, and Kunwi in Kyungsang Puk Do province, South Korea, and 237 males and 219 female of the same ages born and reared at Taegu in families of "rural to urban migrants." Comparisons were made between urban and rural groups for measures of body size and form, skinfold thickness, the body mass index (BMI), and estimated arm muscle area (ARM). Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Normative data for Korean children with regard to average height were sourced from the University of Minnesota international adoption clinic growth chart for Korean boys and girls. The average age of menarche was 12.5±2 years for Korean girls25,26.…”
Section: Methodsmentioning
confidence: 99%
“…Normative data for Korean children with regard to average height were sourced from the University of Minnesota international adoption clinic growth chart for Korean boys and girls. The average age of menarche was 12.5±2 years for Korean girls25,26.…”
Section: Methodsmentioning
confidence: 99%
“…Studies by Goldstein, (1971), Prasad et al (1971), Banik et al (1972), Eleveth and Tanner, (1991) concluded that children belonging to higher and middle socioeconomic groups are larger in body size than those in lower socio-economic groups. Kim et al (2002) also suggested that presumably, amenities that contribute to "quality of life" are, on average, more accessible to urban than to rural children. Studies by Rona and Chinn (1986), Berdasco (1994), Naidu and Rao (1994) showed that increase in anthropometric measurements is associated with the families having higher educational and income status.…”
Section: Resultsmentioning
confidence: 99%